Abiotic stress tolerant Trichoderma harzianum strain for growth promotion and foot rot management in black pepper - V.S. Sujatha, K.M.D. Devi, D.Girija, R. Sri Vithya, K. Surendra Gopal, (Journal of Plantation Crops, 2018)
A study was conducted to evaluate and identify an abiotic stress tolerant PGPR and Trichoderma sp. for growth promotion and foot rot management in black pepper (Piper nigrum L.). The study found Trichoderma harzianum (CKT isolate) as the most abiotic stress tolerant isolate for growth promotion and Phytophthora management in black pepper nursery maintained under polyhouse conditions (elevated temperature up to 41 oC). In the case of ambient condition (up to 29.7 oC), Pseudomonas fluorescens (PAP isolate) was the most promising isolate. However, considering both natural and polyhouse conditions and per cent disease incidence, T. harzianum (CKT isolate) was the most promising high temperature tolerant culture for growth promotion and disease management in black pepper nursery.